If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1t = 5x + 9 Reorder the terms: -1t + 3x = 5x + 9 Reorder the terms: -1t + 3x = 9 + 5x Solving -1t + 3x = 9 + 5x Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3x' to each side of the equation. -1t + 3x + -3x = 9 + 5x + -3x Combine like terms: 3x + -3x = 0 -1t + 0 = 9 + 5x + -3x -1t = 9 + 5x + -3x Combine like terms: 5x + -3x = 2x -1t = 9 + 2x Divide each side by '-1'. t = -9 + -2x Simplifying t = -9 + -2x
| -10r-15=3(11-4r)-58 | | f=1500+-160x+4x^2 | | 2x+2x-7=9 | | 31-9j=-277 | | -11r=2 | | -5(2x+4)=-5x-10 | | 3(6x^2+5x-1)= | | 9y+x=4 | | (X-14)+146=180 | | 1.025x+2.458=7.585 | | 2(x-5)-6=5x-3(4+x) | | (2x-8)(x+7)=11x+7 | | 3985.5=160(x) | | -22n-4n=-36 | | 1=7.14b(-7.1b) | | 3(x+6)=3(x+10) | | 10+4p=86 | | 64x+70=180 | | 5-3x=-26 | | 2(6-5x)=5x+9 | | 48-n^2=2n | | [-9]-[-8]= | | 6y+36=9y | | 5(x+7)=5(x+11) | | 3x-9=75-9x | | 2(x+6)=5x+9 | | (21+10)-9j=-277 | | 0=x^2+38x | | 8-10x=6x+1 | | 9x+3-10=3(3+x) | | 1=a(0+b)(0-7.1) | | ln(x)=3.78 |